Synthesis of Nanoparticle-based Binary Oxide Electrode TiO2-ZrO2 with Carrot-derived Natural Dye Extract for Dye Sensitized Solar Cell (DSSC) Application - Win, S.Y.; Win, T.T.; Maung, Y.M.; Soe, K.K.K.; Kyaw, T.T.; Tan, C.K.; Sokkalingam, Rajalingam; Oo, Zeya (University Putra Malaysia Press, 2015)
Dye-sensitized solar cell (DSSC) is the third generation of thin film solar cell. In this work, carrot fruit dye has been prepared and used in the DSSC as sensitizer. TiO2–ZrO2 fine binary oxide was mechanochemically prepared and made paste. Then, TiO2–ZrO2 paste (colloidal) was deposited onto FTO/glass in two ways as single and double coatings by rolling method. It was immersed in the carrot solution to get dyed cell. The dyed TiO2-ZrO2-FTO/glass cell was offset with the FTO/glass cell coated with adhesive carbon paste. Photovoltaic properties of prepared TiO2–ZrO2 DSSC cell were measured. The results showed the efficiency of double coating cell was found to be larger than that of the single coating cell. According to the fill factor from experiments, both DSSC cells were acceptable for industrial requirement. It can be concluded that the results obtained were quite acceptable in use of cost-effective and Eco-favorable dye-sensitized solar cell.